2021
DOI: 10.1111/mcn.13163
|View full text |Cite
|
Sign up to set email alerts
|

Associations between livestock ownership and lower odds of anaemia among children 6–59 months old are not mediated by animal‐source food consumption in Ghana

Abstract: Livestock ownership may mitigate anaemia among young children by providing access to animal-source foods (ASFs) yet exacerbate anaemia by exposing children to animal-source pathogens. This study aimed to assess the association between household livestock ownership and child anaemia and examine whether this relationship is mediated by child ASF consumption or by child morbidity and inflammation. We conducted a cross-sectional study of 470 children aged 6-59 months in Greater Accra, Ghana. Child blood samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 68 publications
0
5
2
Order By: Relevance
“…Furthermore, the short observation time or cross-sectional nature of the study design may have concealed some of these effects that may have been detected using other study designs/ methods. This finding is also different from other studies that reported either beneficial (positive) (Lambrecht et al, 2021) or adverse (negative) associations (Christian et al, 2019;Jones et al, 2018) between livestock ownership and anemia risk among children in LMIC settings.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the short observation time or cross-sectional nature of the study design may have concealed some of these effects that may have been detected using other study designs/ methods. This finding is also different from other studies that reported either beneficial (positive) (Lambrecht et al, 2021) or adverse (negative) associations (Christian et al, 2019;Jones et al, 2018) between livestock ownership and anemia risk among children in LMIC settings.…”
Section: Discussioncontrasting
confidence: 99%
“…However, studies on the role of livestock ownership and child anemia have yielded conflicting findings. For example, in some studies (Christian et al, 2019 ; Jones et al, 2018 ), aggregate livestock ownership was associated with higher odds of child anemia; while another study (Lambrecht et al, 2021 ) with a lower risk (Lambrecht et al, 2021 ). In Asian countries like Bangladesh, Cambodia, Nepal, and Philippines, a homestead food production model that included animal production improved household food security and lowered the risk of anemia by improving nutrient density (Talukder et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chicken ownership was not associated with lower hemoglobin concentrations among children in Sub-Saharan Africa [ 80 ]. A recent study in Ghana found lower odds of anemia among children from households owning cattle, small livestock (goats, sheep, or pigs), and poultry than those owning no livestock [ 33 ]. We reported a marginally significant reduction of anemia in our pilot project [ 29 ] in which less than 6% of intervention households used separate chicken shelters at baseline, which increased to 25% at 6 months [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to economic reasons, most cages were made from farm leftover stalks of maize and sorghum that were not strong enough to last long [ 30 ]. Observational studies in Sub-Sahara Africa associated livestock ownership including poultry with anemia and lower hemoglobin [ 31 , 32 ] although this was not always the case [ 33 ]. Taking the challenges related to the construction of separate chicken shelters observed in the pilot study and the probable negative effect of rearing chickens on child health and nutrition outcomes including masking of intervention effects into consideration, this project provided cages beside chickens to minimize the disease risk from direct contact with the birds and their feces.…”
Section: Introductionmentioning
confidence: 99%
“…This study analyzed a subsample of children from a larger study investigating livestock ownership and anemia. 37 Briefly, children were sampled in 18 communities within the Ga East and Shai Osudoku Districts of Greater Accra, with communities purposefully selected for variation in types of livestock being reared and community size. Ga East is a primarily urban district with about 6% of its population engaged in agriculture.…”
Section: Methodsmentioning
confidence: 99%